Dependence of the stored charges and tunneling voltages on the tunneling SiO2 thickness for Si nanoparticles embedded in a SiO2 layer - Oh, Do-Hyun; Lee, Soojin; Cho, Woon-Jo; Kim, Tae Whan (ELSEVIER SCIENCE BV, 2008)
Dependence of the stored charges and the tunneling voltages on the tunneling SiO2 thickness for Si nanoparticles embedded in a SiO2 layer formed by the sonochemical method was investigated by using electrostatic force microscopy (EFM) measurements. Bright-field transmission electron microscopy images showed that Si nanoparticles were embedded in a SiO2 layer. EFM images for the Si nanoparticles embedded in a SiO2 layer under applied bias voltages showed that the localized charges remained in the Si nanoparticles embedded in. a SiO2 layer. The stored charge in the Si nanoparticles embedded in a SiO2 layer increased with a decrease in the tunneling SiO2 thickness. While the threshold tunneling voltage increased with an increase in the tunneling oxide thickness, the mean amplitude of the tunneling voltage increased with a decrease in the thickness of the tunneling SiO2 layer. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: SILICON NANOPARTICLES; FORCE MICROSCOPY; RETENTION-TIME; NANOCRYSTALS; MEMORY; INJECTION; CHANNEL